PENDAMPINGAN KADER DALAM SKRINING FAKTOR RESIKO PENYAKIT TIDAK MENULAR DALAM MASA PANDEMI COVID-19 - Rizky Amelia; Erna Wudyastuti; Isharyanti, Septalia (LPPM STIKES Madani, 2023)
Non-communicable diseases are global problems that needed special attention. One of the efforts in non-communicable disease screening held in Posbindu is to prevent the increase in mortality and morbidity rates. The active role of health cadres at Posbindu was needed, so encouragement was needed in screening risk factors for non-communicable diseases. The purpose of this community service was to increase the knowledge and abilities of health cadres in identifying risk factors for communicable diseases at Posbindu. The method in this service activity was cadre assistance, which consisted of educational and evaluation activities regarding non-communicable diseases and posbindu. The result was that the majority of the knowledge at the pretest had sufficient knowledge of 50%, and at the posttest, the majority of the knowledge had good knowledge of 59.1%. The conclusion of this community service was an increase in the knowledge of health cadres regarding risk factors for non-communicable diseases, as indicated by the pretest mean value of 9.95 to 13.59 during the posttest. In addition, cadres could carry out health examinations and screen risk factors for non-communicable diseases at Posbindu.